PADDY’S PERFORMANCE IN MALAYSIA - Noorfazreen Mohd Aris; Mohd Faizal P.Rameli; Norizah Mohamed @ Haji Daud; Sharipah Amirah Haji Abas; Norajila Che Man (Journal of Islamic, Social, Economics and Development, 2018)
Paddy is an important food commodity in Malaysia. In order to materialize government’s attention on this matter, some policies have been constructed. Starting off with First National Agricultural Policy (NAP1) in 1984, it is then followed by Second National Agricultural Policy (NAP2) in 1992, Third National Agricultural Policy (NAP3) in 1998 and National Food Security Policy (NFSP) in 2008 as well as National Agrofood Policy (NAP) which has been implemented from 2011 until present. Insufficiency of this main food source will result in food deprivation throughout the country, leading to the need of importation. In relation to that, this research focused on the statistic of paddy production within the policies’ implementation period from 1984 until 2015. This qualitative research uses library research Volume: 3 Issue: 11 [June, 2018] pp. 51-61] Journal of Islamic, Social, Economics and Development eISSN: 0128-1755 Journal website: www.jised.com m52 approach to collect data which involves a lot of materials including the 5th-11th Malaysia Plan, DPN1 until DPN3 and economy reports. Data collected were analysed via content analysis method. From the data, research finds that the development of paddy agricultural sector is on rise but still inadequate to support nation’s need and its dependability on importation.